Courage: an Ambivalent and Elusive Virtue - Zavaliy, Andrei (2025)
The epilogue provides a brief overview of all the contributions to the volume, bringing into sharp focus the theoretical complexity and definitional elusiveness of the concepts of courage and cowardice in the ancient world. The article further connects the topic under discussion with similar themes discussed by other authors in the book. Such cross-referencing sets the proper context for the analysis and assists the reader interested in a particular layer of ancient culture or in a certain period in locating all the relevant articles. Furthermore, several suggestions are made for future paths of research in the area and questions are raised in connection with the author’s main thesis, pointing to aspects of the problem that could be explored at greater depth. The final section envisions a more global approach to the concept of courage that should consider the ancient sources beyond the Mediterranean world for potentially prolific cross-cultural comparative study.